THE DEVELOPMENT OF PENETRATION CHARGES FOR INCREASING THE EFFICIENCY OF THE INTERVENTIONS OF FIRE RESCUE SERVICE UNITS - Stanislav LICHOROBIEC; Karla BARČOVÁ; Ladislav ŘÍHA (Transactions of the VŠB: Technical University of Ostrava, Safety Engineering Series, 2019)
During building fires is often necessary to deliver nozzles with water to the desired point of intervention and the wall or ceiling must be penetrated for energy supply and the entrance of persons. Access openings for extinguishing are created with hand tools or explosives, but it is a very time-consuming activity and fragmented material may endanger persons. Another possibility is the use of charges with a water layer, which absorbs the shock wave of the explosion at the back and at the same time significantly suppresses the fragmentation of the building element on which the charge acts. The penetration charge developed in two versions allows a sufficient penetration of the partition wall.